Betavoltaic-powered electrochemical cells using TiO2 nanotube arrays incorporated with carbon nanotubes. (15th June 2022) - Wang, Na; Zheng, Renrong; Chi, Tianxi; Jiang, Tongxin; Ding, Zan; Li, Xin; Liu, Shichao; Zhang, Lifeng; San, Haisheng
Abstract: Highly efficient direct energy conversion utilizing the betavoltaic effect is a promising alternative for developing of maintenance-free and long-life self-generating power cells. This work demonstrates a betavoltaic-powered electrochemical cell (BPEC) using free-standing TiO2 nanotube arrays (TNTAs) incorporated with single-wall carbon nanotubes (SWCNTs) as the beta anode, a polyiodide ( I − / I 3 − ) solution as the electrolyte, and a radioisotope 63 Ni/Ni sheet as the cathode as well as the irradiation source. Freestanding TNTAs were fabricated using electrochemical anodization. Monte Carlo simulations were used to investigate the interaction of the incident beta particles with the TNTAs structure. Experimentally, the photoelectrochemical characteristics were used to optimize the structural design of the BPECs. The optimum BPEC exhibited an energy conversion efficiency of 8.74% with an open circuit voltage of 0.26 V and a short circuit current density of 0.87 μA/cm 2 . The enhanced betavoltaic effect is attributed to the highly efficient separation and transport of beta-generated carriers through the enhanced beta-electrochemical redox reactions in the 3-D TiO2 /liquid heterojunction as well as the extensive SWCNTs conductive network. Graphical abstract: Image 1 Highlights: Monte Carlo simulation is used to investigate the interaction of beta particles with energy conversion structures. TNTAs incorporated with SWCNTs were used as the beta-anode of BPECs. Photoelectrochemical performance is used to evaluate and optimize the structure design of BPECs. Beta-excited electrochemical reaction is enhanced by the 3-D TiO2 /liquid heterojunction and SWCNTs conductive network.